Biomonitoring in Limnic Environments: A Scientometric Approach - Gomes, Leonardo Fernandes; Pereira, Hasley Rodrigo; Barbosa, Hugo de Oliveira; de Souza, Carla Albuquerque; Vieira, Ludgero Cardoso Galli (Fronteira: Journal of Social, Technological and Environmental Science, 2020)
In the face of increasing human impacts, biomonitoring emerges as an approach to evaluate the status of these ecosystems. Our purpose was to evaluate the publications on biomonitoring in limnic environments and to answer the following questions: (i) What are the approaches in biomonitoring studies around the world? (ii) Are the countries’ human development index (HDI) and the available water volume capable to influence publications on biomonitoring? (iii) How are distributed biomonitoring publications by biological groups (e.g., fish, plants, phytoplankton, zooplankton, periphyton, insects) and by environments (lotic and lentic)? To access the publications about biomonitoring in limnic environments, we performed a search in the Web of Science database, restricted between 1991 and 2016. The scientific interest in biomonitoring in limnic environments showed an increasing trend over the years. Furthermore, the countries that presented the highest number of biomonitoring publications had also high HDI values, which reflected high investments in research and development or specific legislation for water quality monitoring. Despite the significant relationship, the water volume was not a major factor influencing the research development. Our study revealed that fish, macroinvertebrates, and lotic environments were the most used for biological monitoring purposes.